Trends in undergraduate economics degrees: 1991–2015. Issue 4 (1st October 2016) - Siegfried, John J.
ABSTRACT: Undergraduate degrees awarded in economics by U.S. colleges and universities were stagnant from 2009–10 through 2012–13, but have increased rapidly (almost 14 percent) over the two years from 2012–13 through 2014–15.